Single Valued Pentaparitioned Neutrosophic Off-Set / Over-Set / Under-Set - Bimal Shil; Rakhal Das; Suman Das (Neutrosophic Sets and Systems, 2022)
The main focus of this paper is to introduce the notion of single valued pentapartitioned neutrosophic off set / over set / under set. Besides, we establish several operations on single valued pentapartitioned neutrosophic off sets / over sets / under sets. Besides, we furnish some suitable examples to validate the results established in this article. Further, we establish some interesting results on single valued pentapartitioned neutrosophic off set / over set / under set.